2021
DOI: 10.3390/jintelligence9020028
|View full text |Cite
|
Sign up to set email alerts
|

How Is Intelligence Test Performance Associated with Creative Achievement? A Meta-Analysis

Abstract: This paper presents a meta-analysis of the links between intelligence test scores and creative achievement. A three-level meta-analysis of 117 correlation coefficients from 30 studies found a correlation of r = .16 (95% CI: .12, .19), closely mirroring previous meta-analytic findings. The estimated effects were stronger for overall creative achievement and achievement in scientific domains than for correlations between intelligence scores and creative achievement in the arts and everyday creativity. No signs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 110 publications
2
12
0
Order By: Relevance
“…The relationship between cognitive aptitudes and creative achievement test performance was recently meta-analyzed (Karwowski et al, 2021) and confirms an older meta-analysis (Kim, 2008) on the general population (r = 0.16 and r = 0.21 for unreliability corrected effect size). Specifically for science achievement, Karwowski et al (2021) found that r = 0.19, and that this would be larger when corrected. Overall, this suggests moderate to large effect sizes for individual differences research (Gignac and Szodorai, 2016).…”
Section: Creative Achievementsupporting
confidence: 65%
See 2 more Smart Citations
“…The relationship between cognitive aptitudes and creative achievement test performance was recently meta-analyzed (Karwowski et al, 2021) and confirms an older meta-analysis (Kim, 2008) on the general population (r = 0.16 and r = 0.21 for unreliability corrected effect size). Specifically for science achievement, Karwowski et al (2021) found that r = 0.19, and that this would be larger when corrected. Overall, this suggests moderate to large effect sizes for individual differences research (Gignac and Szodorai, 2016).…”
Section: Creative Achievementsupporting
confidence: 65%
“…Beaty et al (2015) also show that these associations increase when the measurement error is accounted for in latent variable models. Karwowski et al (2021) note that a core limitation of the literature reviewed in this area is that much of it has been conducted in the last decade primarily using one measure, the Creative Achievement Questionnaire, which is a self-report instrument (e.g., Carson et al, 2005), and additionally range restriction on the measures used may be an issue.…”
Section: Creative Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Last, real-life creativity is not exclusively predicted by semantic memory. Many other internal and external factors are important to creativity, such as personality, motivation, emotions, and environment ( 1 , 68 , 69 ). Despite these other potential dimensions and sources of variability, the brain connectivity patterns allowed us to predict real-life creativity through the individual differences in semantic memory structure, uncovering its strong influence on creative activities and achievements.…”
Section: Discussionmentioning
confidence: 99%
“…Some variables are closely associated with both creativity and academic achievement: consider intelligence (Deary et al, 2007) or personality traits, such as openness to experience or conscientiousness (Poropat, 2009). Intelligence is the most robust predictor of academic achievement and a systematic correlate of creative abilities (Gerwig et al, 2021) and creative achievement (Karwowski et al., 2021). Openness is considered “a hungry mind trait” (Von Stumm et al, 2011), driving curiosity for learning and personality fuel of creative functioning (S.…”
Section: Creative Abilities and Academic Achievementmentioning
confidence: 99%